TLVs and BEIs 2016 (Cincinnati, 2016)
"The information in this user-friendly, pocket-sized publication is used worldwide as a guide for evaluation and control of workplace exposures to chemical substances and physical agents. Threshold Limit Value (TLV®) occupational exposure guidelines are recommended for more than 700 chemical substances and physical agents. There are more than 50 Biological Exposure Indices (BEIs®) that cover more than 80 chemical substances. Chemical Abstract Service (CAS) registry numbers are listed for each chemical. Introductions to each section and appendices provide philosophical bases and practical recommendations for using TLVs® and BEIs®)."